Analysis of essential oil of Galium verum - Katarzyna Antoniak; Marcin Szymański; Marlena Dudek-Makuch; Wiesława Bylka (Polish Pharmaceutical Society, 2021)
Summary Subject of research. Galium verum L. (lady's bedstraw, yellow bedstraw) (Rubiaceae) is used in folk medicine in dermatoses, bladder and kidneys diseases as well as a choleretic agent. So far, scientific studies have shown as a main constituent: iridoids, flavonoids, phenolic acids and triterpenes. Previous studies confirmed antioxidant, cytotoxic, antimicrobial, hepatoprotective and immunostimulating activities of bedstraw. Aim. The aim of this work was to investigate the chemical profile of essential oil isolated from G. verum collected in Poland. Material and methods. The essential oil was extracted from the herb of G. verum by hydrodistillation in Clevenger-type apparatus and the volatile constituents were identified by gas chromatography coupled with mass spectrometry (GC-MS). Results. 2.60 ml/kg of essential oil was obtained from the of G. verum herb, in which 71 volatile ingredients were identified (100%). According to GC-MS analysis for palmitic acid (10.87%) and anethole (8.39%) as well for menthol (5.28%) and linoleic acid (4.91%) significant amount was noted. In a smaller number were present carvone, β-ionone, phytol, menthone, estragole, linalool and β-farnesene. Terpene compounds represented 31.34% of essential oil, including 9 sesquiterpenes (5.51%), 15 monoterpenes (24.04%), 1 diterpene (1.79%) and 3 phenylpropanoids (10.21%). Among fatty acids fraction was dominated palmitic acid (10.87%) and linoleic acid (4.91%), in the oil were also methyl palmitate (0.41%) and methyl salicylate (0.14%) present. The other active ingredients of the essential oil include: eucalyptol, carvacrol, thujone, camphor, isopulegone, caryophyllene oxide, farnesyl acetate, terpinen-4-ol, γ-terpineol, α-terpineol, myrtenol, methyl salicylate, α-ionone, β-ionone 5,6-epoxide, cis-α-bisabolene, shiobunon, nerolidol and spatulenol. The ingredients of the essential oil are multi-directional activity such as anti-inflammatory, antimicrobial, antiproliferative, proapoptotic, anti-itching, and also affecting the wound healing process. Conclusions. Quantify and a number of ingredients of the essential oil have proven that it may be one of the bioactive important fractions of the bedstraw herb and partly justify the traditional use of G. verum.